Political psychology of border integration - González Riesle, Alvaro (2015)
In order to help establish a Peace Culture in the Peruvian – Chilean border of Tacna - Arica, we propose the implementation of a psychopolitical binational education strategy for peace that will contribute to strengthen the relationship of cooperation between both countries with a view of constructing a future agenda within the framework of the regional integration challenges in the Pacific Alliance.